Rainfall Mapping in Medan Selayang Sub-District using Geographic Information System - Dina Tri Septiningtiyas; Rifka Ananda (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Indonesia is a tropical country which has two seasons, namely the rainy season and the dry season. Rainfall that occurs will vary in each area depending on the altitude of the area, climate, season, and other factors. Medan Selayang Subdistrict is the Subdistrict with the closest distance to the rain station. Where the closer the location of the study area to the rain station, the more accurate the rainfall data obtained will be. One way to make it easier to record and process data is to create a rainfall map by utilizing spatial analysis through a Geographic Information System (GIS). The data in this study are rainfall data and geographic coordinate data obtained from the Meteorology, Climatology and Geophysics Agency in the Medan City area. After data collection, data processing was carried out using the QGIS 3.10 application. with the Inverse Distance Weighted (IDW) interpolation method. From the results of processing rainfall maps in the Medan Selayang sub-district using Inverse Distance Weighted (IDW) interpolation, the rainfall values (rainfall) ranged from 3029.74 mm/year – 3164.20 mm/year.